Marketing Strategy of Gold Savings Products In Increasing The Number of Customers - Marliyah, Marliyah; Rokan, Mustapa Khamal; Tia, Resa Shin; Putra, Irhamsyah (Taqaddum: Community Service Journal, 2024)
Training develops to increase customer with strategy in marketing. Nowadays, every business is concerned about competition. To attract customers, business actors use various marketing techniques, one of which is providing high-quality products. This helps businesses see an increase in the number of clients they serve. This is important because, apart from having an impact on the growth or decline of the company, a well-designed marketing strategy also ensures that the company is ready to face any changes. This is the conclusion drawn from one of Lontaan, Mananeke, and Tawas' previous investigations (2019). In the contemporary business landscape, companies must progressively develop their existing businesses with well-designed marketing strategies to ensure their survival.